Calcium Ion Chelation Preserves Platelet Function During Cold Storage. Issue 1 (January 2021) - Xiang, Binggang; Zhang, Guoying; Zhang, Yan; Wu, Congqing; Joshi, Smita; Morris, Andrew J.; Ware, Jerry; Smyth, Susan S.; Whiteheart, Sidney W.; Li, Zhenyu
Abstract : Objective: Platelet transfusion is a life-saving therapy to prevent or treat bleeding in patients with thrombocytopenia or platelet dysfunction. However, for >6 decades, safe and effective strategies for platelet storage have been an impediment to widespread use of platelet transfusion. Refrigerated platelets are cleared rapidly from circulation, precluding cold storage of platelets for transfusion. Consequently, platelets are stored at room temperature with an upper limit of 5 days due to risks of bacterial contamination and loss of platelet function. This practice severely limits platelet availability for transfusion. This study is to identify the mechanism of platelet clearance after cold storage and develop a method for platelet cold storage. Approach and Results: We found that rapid clearance of cold-stored platelets was largely due to integrin activation and apoptosis. Deficiency of integrin β3 or caspase-3 prolonged cold-stored platelets in circulation. Pretreatment of platelets with EGTA, a cell impermeable calcium ion chelator, reversely inhibited cold storage-induced platelet activation and consequently prolonged circulation of cold-stored platelets. Moreover, transfusion of EGTA-treated, cold-stored platelets, but not room temperature-stored platelets, into the mice deficient in glycoprotein Ibα significantly shortened tail-bleeding times and diminished blood loss. Conclusions: Integrin activation and apoptosis is the underlying mechanism of rapid clearance of platelets after cold storage. Addition of a cell impermeable calcium ion chelator to platelet products is potentially a simple and effective method to enable cold storage of platelets for transfusion. Abstract : Supplemental Digital Content is available in the text.